Women’s views on anxiety in pregnancy and the use of anxiety instruments: a qualitative study - Evans, Kerry; Morrell, C. Jane; Spiby, Helen (Taylor & Francis, 2016)
Objective: To explore women’s experience of anxiety in pregnancy and views on the use of anxiety instruments in antenatal care.